The development of a system of 24 hours preservation of the heart for transplantation - Wicomb, Winston Neville (Division of Cardiology, 2017)
This thesis describes a series of investigations into the problems that hamper the progress of myocardial preservation for transplantation in man. Six positive aspects of cardiac preservation have emerged from this study: - (1) A clear fluid hyperosmolar solution was formulated that adequately preserved viability of pig and baboon hearts. (2) A pneumatically powered portable preservation unit was designed which successfully preserved pig and baboon hearts when assessed by either functional testing or orthotopic transplantation. (3) A method of in vitro testing of hearts was developed that correlated with results from orthotopic transplantation. (4) A technique of cardiac autotransplantation in baboons was perfected. (5) The high release of lysosomal acid phosphatase during the period of hypothermic preservation was shown to be non-pathological and was reversible after a period of warm blood perfusion. (6) Successful preservation of human hearts for periods longer than 4 hours, not previously achieved, was obtained. The preservation solution and the portable preservation unit that emerged from this experimental study were thoroughly investigated before clinical application. During the development of this perfusate the author had numerous consultations and discussions with colleagues and senior members of neighbouring departments.